"Check the grade, log out": students' engagement with feedback in learning management systems. Issue 4 (19th May 2021) - Winstone, Naomi; Bourne, Jessica; Medland, Emma; Niculescu, Irina; Rees, Roger
Abstract: There is growing recognition that socio-constructivist representations of feedback processes, where students build their own understanding through engaging with and discussing feedback information, are more appropriate than cognitivist transmission-oriented models. In parallel, practice has developed away from hard-copy handwritten or typed feedback comments, towards the provision of e-feedback in learning management systems (LMS). Through thematic analysis of activity-oriented focus groups with 33 undergraduate students, the present study aimed to explore 1) students' experience of engaging with feedback in the LMS; 2) barriers to students' engagement; and 3) students' perceptions of the potential for technology to ameliorate these barriers. The data reveal particular barriers to engagement created by the LMS environment; grades and feedback are commonly separated spatially, limiting attention to the latter. Additionally, the distributed location of feedback from different tasks limits synthesis of feedback. Nevertheless, students perceived that the LMS environment affords opportunities for addressing such challenges, particularly in relation to the potential for a tool to synthesise feedback information across modules, and to direct students to resources to develop their skills. The findings are discussed in the context of cycles of engagement with feedback, and implications for the principled use of technology in feedback processes are discussed.